Średniowieczne wraki z półwyspu Falsterbo (Szwecja) - Ossowski, Waldemar; Krąpiec, Marek; Nilsson, Marcus (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2003)
In the 14th-15th centuries the largest herring fisheries could be found on the south-western Scandinavian Peninsula shores. Each year the hanseatic cities organized periodical purchases of herring caught by local fishermen, the fish were cured in barrels and many craft goods were sold during summer and autumn fairs. During the archaeological works conducted in theFalsterbo castle ruins in 1911 six wooden barges and in 1993 the remains of cog like vessels were found. The aim of this paper is to present information on the building and chronology of the wreck that were discovered there. The conducted dendrochronological analysis show that the wood used to build the barge originates from trees which were cut down after 1344, mostprobably in the late 40s of the 14th century in the vicinity of Gdańsk. This is the earliest at the moment example of exports of timbers from Gdańsk - Pomerania region
il. ; 29 cm
Keywords: średniowiecze; szkutnictwo; dendrochronologia; Falsterbo; handel drewnem; okręty; kogi; metody uszczelniania